2015
DOI: 10.1111/apm.12455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron on expression of efflux pump (adeABC) and quorum sensing (luxI, luxR) genes in clinical isolates of Acinetobacter baumannii

Abstract: Resistance-nodulation-division efflux system (RND) adeABC contributes to intrinsic resistance to various drug classes in Acinetobacter baumannii. Similarly, quorum sensing (QS) plays an important role in the biofilm formation and pathogenicity of this bacterium. The aims of this study were to evaluate the influence of iron limitation on the expression of efflux pump (adeABC) genes and QS (luxI, luxR) system by relative quantitative real-time polymerase chain reaction (qRT-PCR). In addition, DNA sequence and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…In this study, we found that all the isolated strains were susceptible to tigecycline and colistin. However, there have been many reports of tigecycline and colistin resistance, which range from 0.6% to 45.8% [18][19][20][21] and 0 to 30.6%, respectively, around the world [22][23][24][25]. Furthermore, colistin resistance was reported to be of 4% in the EARS-Net 2016 report [26].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that all the isolated strains were susceptible to tigecycline and colistin. However, there have been many reports of tigecycline and colistin resistance, which range from 0.6% to 45.8% [18][19][20][21] and 0 to 30.6%, respectively, around the world [22][23][24][25]. Furthermore, colistin resistance was reported to be of 4% in the EARS-Net 2016 report [26].…”
Section: Discussionmentioning
confidence: 99%
“…In some studies the adeB gene was found in all clinically isolated strains, while in other studies the rate just was 70% to 75% [13], [14]. By contrast, some studies found that adeA has the highest detection rate in clinically isolated strains [15], [16]. More researchers incline to the view that adeB is the most important gene in adeABC and is most associated with the resistance of A. baumannii [17].…”
Section: Structure and Regulator Of Adeabcmentioning
confidence: 98%
“…A report of Poole and colleagues [266] suggested that the MexAB-OprM efflux system is of crucial importance in P. aeruginosa survival under iron restrictions, as it is overexpressed under these circumstances. Furthermore, it was demonstrated that iron limitation has positive effects on the expression of both EPs ( ade ABC) and QS genes ( lux I/R) in A. baumannii , suggesting their regulatory role in these systems [267]. A surface protein named Bap, which is involved in A. baumannii biofilm formation (it helps in cell-cell adhesion and biofilm maturation), was also identified in strong biofilm formers in the described conditions [267].…”
Section: Plant-based Strategies To Deal With Unwanted Biofilmsmentioning
confidence: 99%